ANALYSIS OF ACCIDENT AT THE PRESENTATIONS IN THE FIELD OF ŽSR (Perner's Contacts, 2018)
The contribution briefly describes the accident at crossings in the ŽSR administration within the Slovak Republic, following which the analysis determines the relation between the number of registered vehicles and the number of accidents on crossings together with the accepted proposal for their possible elimination
Keywords: railway network; crossroad; accident; road vehicle; train